2021
DOI: 10.3390/ijerph18041915
|View full text |Cite
|
Sign up to set email alerts
|

An Experience of Public Dental Care during the COVID-19 Pandemic: Reflection and Analysis

Abstract: Since its emergence in China, the COVID-19 pandemic has become the number 1 health challenge in the world with all affected countries trying to learn from each other’s experiences. When it comes to health services, dental care does not seem to be a priority area, despite the fact that it is among the highest risk medical specialisations in terms of spreading the infection. Using the Department of Community Dentistry of Semmelweis University as a case study, the objective of this paper is to introduce and analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…42 Mind, the mental health charity, found that a third of adults did not access support because they did not think that their issue was serious enough. 43 They also found the key challenge was to ensure those who want to access services know that they deserve support. 28 Several survey participants stated felt that 'others have it worse' and that they needed to 'suck it up' or 'get on with it' .…”
Section: Perception Of Stress During the Pandemicmentioning
confidence: 99%
“…42 Mind, the mental health charity, found that a third of adults did not access support because they did not think that their issue was serious enough. 43 They also found the key challenge was to ensure those who want to access services know that they deserve support. 28 Several survey participants stated felt that 'others have it worse' and that they needed to 'suck it up' or 'get on with it' .…”
Section: Perception Of Stress During the Pandemicmentioning
confidence: 99%
“…In terms of visits, research in the US recorded a 33% decrease in the number of visits to dental clinics in March -August 2020 compared to the corresponding period in 2019 [19]. Correspondingly, lower dental visits in 2020 were found in surveys in Hungary [20], India [21] and Australia [22]. In England, 21 million adults had seen a dentist within the last two years in June 2020 (47.7% of the population).…”
Section: Discussionmentioning
confidence: 97%
“…It came into limelight in December, 2019 and was declared a global pandemic by the World Health Organization (WHO) [ 3 , 4 ]. Since its emergence, this pandemic has spread worldwide has become the number one health challenge [ 5 , 6 ]. The virus can potentially spread through droplets or by usual contact [ 7 ].…”
Section: Introductionmentioning
confidence: 99%